2005
DOI: 10.1007/s11138-005-5592-4
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Private Schools Serving Low-Income Families in Andhra Pradesh, India

Abstract: This paper sets out some findings of a research project carried out in private unaided schools in low-income areas of Hyderabad, India. The part of the research project documented here was designed to examine the question: ‘Is the regulatory regime conducive to entrepreneurial action and market discovery’ with particular reference to the low-income schools in Hyderabad. This paper is narrowly focused, setting out the results of pattern matching empirical data with the Austrian economic concepts of entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The majority of government schools reported that they were Urdu medium (72.6%). Observations in classrooms for earlier research suggest that schools describing themselves as English-medium use English only textbooks for all subjects apart from Indian languages, with teachers offering a mixture of English and Urdu/ Telugu to support their use (Dixon & Tooley, 2005;Smith et al, 2005).…”
Section: Medium Of Instructionmentioning
confidence: 99%
“…The majority of government schools reported that they were Urdu medium (72.6%). Observations in classrooms for earlier research suggest that schools describing themselves as English-medium use English only textbooks for all subjects apart from Indian languages, with teachers offering a mixture of English and Urdu/ Telugu to support their use (Dixon & Tooley, 2005;Smith et al, 2005).…”
Section: Medium Of Instructionmentioning
confidence: 99%
“…James Tooley and his colleagues at the University of Newcastle are widely published advocates of LFPSs. In a proliferation of research publications based on studies in countries including China, Ghana, India, Kenya, and Nigeria, they (Dixon & Tooley, 2005;Tooley, 2013;Tooley & Dixon, 2005a, 2005b, 2005cTooley, Dixon, & Gomathi, 2007;Tooley, Dixon, Shamsan, & Schagen, 2010;Tooley, Dixon, & Stanfield, 2008) make a range of assertions. They describe how low-cost private schools have been serving the needs of the poor for many years and were largely unacknowledged by the education authorities in many countries until the early 2000s (Tooley, 2009).…”
Section: Key Debatesmentioning
confidence: 99%
“…India provides an example of the complexities of government regulation of private schools and the limitations in compliance (Dixon & Tooley, 2005). Private schools are prohibited from making a profit from education or from "commercializing" the service.…”
Section: Registration Regulation and Facilitationmentioning
confidence: 99%
“…Over and above the curriculum, every school board also set guidelines on a school's physical and human infrastructural requirements. Though, in practice these rules on infrastructure are more often followed in breach than in compliance (Dixon & Tooley, 2005 …”
Section: Academic Governance Of Indian Schoolsmentioning
confidence: 99%